Reflections on the Discipline of Psychology in the Law Course - Barros Filho, Geraldo Carreiro de; Oliveira, Gislene Farias de (Amadeus International Multidisciplinary Journal, 2016)
This article discusses questions about the discipline of Psychology, taught in many law schools in the region of the state of Ceará and surroundings of Cariri region. While retaining certain tradition, almost unchanged in terms of teaching methodology, a situation which, in a way, paralyzes its didactic, not always allowing an evolutionary bias of the legal postpositivism and transdisciplinary. Both salutary to survival and necessary changes to an adjustment to the labor market and the contemporary higher graduation academies. The exercise of the function does not dispense with critical view of legal epistemology. That, even though incipient in our institutions of higher education, as in many cases, it requires "knowledge by heart" in many cases. The results indicate the need for greater investment in crosscutting legal education, where psychological science has a key space; although in reality only take part in a minimum of 1.78% percentage of class hours, on average, a total 4,500 class hours in undergraduate courses.